PENGARUH LOKASI BISNIS TERHADAP PENDAPATAN DAN KEUNTUNGAN UMKM : STUDI KASUS BARUGA STREET FOOD PALU - Nuraisyah Nuraisyah; Gita Farista; Syarif Permana Salingkat; Mohamad Risky Adhitya; Nur wahdania; Rena Rena; Arifah Rahmadhani (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This research aims to understand how business actors at baruga street food palu view the influence of business location on their income and profits. Thorough in-depth interviews, this research found that business location greatly influences the number of visitors and turnover. Business actors in strategic location tend to have wider networks and are able to retain costumers. Where a location will greatly influence the income of MSME business actors if it has a very strategic location in marketing their business by taking advantage of the large number of people who visit Baruga Street Food In Palu.